Prognosticating COVID Therapeutic Responses: Ambiguous Loss and Disenfranchised Grief - Kaur-Aujla, Harjinder; Lillie, Kate; Wagstaff, Christopher (Frontiers in Public Health, 2022)
Abstract Conventionally, therapeutic assessments, interventions, and treatments have focussed on death-related 'losses and grief' responses. It is purported that the Covid-19 aftermath has resulted in losses that cannot always be encapsulated using this method. In search of reasoning, models and theories that explain the sweeping mass destruction that Covid- 19 has caused, key concepts arise in terms of how we should deal with losses and in turn support patients in the health and social care sector, (notwithstanding formal therapeutic services). There is a crucial need to embrace ambiguous loss and disenfranchised grief into everyday terminology and be acquainted with these issues, thereby adapting how services/ clinicians now embrace loss and grief work. Integral to this process is to recognise that there has been a disproportionate impact on Black and minority ethnic communities, and we now need to ensure services are 'seriously culturally competent'. Primary Care services/ IAPT/ health and social care/ voluntary sector are all likely to be at the forefront of delivering these interventions and are already established gatekeepers. So, this article discusses the prognostic therapeutic response to non-death related losses and grief, not restricted to the formal echelons of therapeutic provision.